Allometry for Sexual Size Dimorphism in Stoneflies Defies the Rensch's Rule - Guillermo-Ferreira, R. [UNESP]; Novaes, M. C. [UNESP]; Lecci, L. S. [UNESP]; Bispo, Pitágoras da Conceição [UNESP] (Entomological Soc Brasil, 2014)
The Rensch's rule predicts that male-biased sexual size dimorphism (SSD) increases with body size, while female-biased SSD (FBSSD) decreases. In insects, many groups follow this rule, but the evidence suggests that it is taxon dependent and that the inverse of the rule can occur in species with FBSSD. Therefore, we conducted this study with Gripopterygidae stoneflies (Plecoptera) to describe their pattern of SSD and determine if they follow the Rensch's rule. Our data suggest that stoneflies exhibit FBSSD and do not follow the rule, but a reverse pattern. Our results corroborate other studies that suggest that the Rensch's rule is taxon based and that groups with FBSSD usually fail to obey the rule.
Keywords: Allometry; body size; Gripopteryx; sexual selection; stonefly